ANALYSIS OF HARMONY IN MOVEMENT AND SOUND: SPIRITUAL MEANING LET ALL PRAISE GOD - Levinson Y A Simaela; Junita Batubara; Dewi Tika Lestari (RADJA PUBLIKA, 2025)
This study discusses a comprehensive analysis of the choral work